Evaluation of reference genes for gene expression analysis in Japanese flounder (Paralichthys olivaceus) under temperature stress - Ping Han; Jianming Chen; Zhennan Sun; Shengjie Ren; Xubo Wang (BMC Genomics)
Abstract Background Quantitative Real-time PCR (qRT-PCR) is a powerful technique to analyze gene expression patterns by measuring the relative abundance of mRNA transcription levels. The most crucial step in obtaining accurate results of qRT-PCR is to select suitable reference genes. Water temperature is an important factor that affects various physiological processes of fish. Presently, Japanese flounder is a commercially important marine culture species and the study of its gene expression is increasing rapidly. However, the reference genes used for Japanese flounder in previous studies, especially under temperature stress, only focused on those well-known genes widely reported in vertebrates, which might not be the proper reference genes. Results In this study, we evaluated the suitability of eight genes including ribosomal protein L6 (rpl6), ribosomal protein L9 (rpl9), delta (4)-desaturase, sphingolipid 1 (degs1), cathepsin L (ctsl), eukaryotic translation elongation factor 1 gamma (eef1g), NSA2 ribosome biogenesis homolog (nsa2), eukaryotic translation initiation factor 3, subunit E, a (eif3ea), glutamine amidotransferase class 1 domain containing 1 (gatd1) analyzed from RNA sequencing (RNA-Seq) data and two genes including β-actin (actb) and 18S rRNA ribosomal RNA (18S RNA) selected from literature to obtain the best internal controls in qRT-PCR analysis of Japanese flounder under temperature stress. The statistical analysis methods (delta-Ct, BestKeeper, geNorm, and NormFinder) were further used to determine candidate reference gene stability. Initial results showed the suitability of eight genes from RNA-Seq data, which exhibited more stable expression levels than two commonly reported reference genes. Further analysis revealed that gatd1 and rpl6 were the best reference genes in Japanese flounder exposed to temperature stress. Conclusion This study transcriptome-wide identified reference genes in different tissues of Japanese flounder exposed to temperature stress for the first time, providing a basis for gene expression research in flatfish.